Hubungan Antara Harapan Dengan Quarter Life Crisis Pada Mahasiswa Yang Mengalami Toxic Relationship - Setiawan, Nugroho Arief; Milati, Alfia Zahrotu (ANFUSINA: Journal of Psychology, 2022)
Quarter life crisis is an emotional crisis experienced by individuals who are in the transition phase from adolescence to early adulthood (emerging adulthood). Students as individuals in their early adulthood need to have a solution in order to properly deal with this quarter life crisis period. Hope can reduce distress and foster a positive effect. The purpose of this study was to determine the relationship between hope and quarter life crisis in students who experience toxic relationships. The population in this study were students of the State Islamic University of Raden Intan Lampung. The sampling technique used is purposive sampling. The sample in this study amounted to 92 respondents. The measuring tools used are the quarter life crisis scale and the expectation scale. The analysis technique used is product moment correlation with the help of IBM SPSS ver 25 software for windows. The results showed that the majority of students were in the moderate category of quarter life crisis where women were higher than men. The expectation variable shows that the expectations that students have are mostly in the moderate category, both are in the same category. The results of the analysis show that expectations have a significant negative effect on the quarter life crisis (R= -0.431, R Square= 0.185, p < 0.01), which means that the higher the expectation, the lower the quarter life crisis experienced. And conversely, the lower the expectation, the higher the quarter life crisis experienced. Judging from the value of R Square, the expectation has an effect of 18.5% on the quarter life crisis, and the other 81.5% is influenced by other variables outside the study.Key Word: Hope, Quarter Life Crisis, Toxic Relationship